Calcium phosphate-based composites as injectable bone substitute materials - Low, Kah Ling; Tan, Soon Huat; Zein, Sharif Hussein Sharif; Roether, Judith A.; Mourino, Viviana; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2010)
A major weakness of current orthopedic implant materials, for instance sintered hydroxyapatite (HA), is that they exist as a hardened form, requiring the surgeon to fit the surgical site around an implant to the desired shape. This can cause an increase in bone loss, trauma to the surrounding tissue, and longer surgical time. A convenient alternative to harden bone filling materials are injectable bone substitutes (IBS). In this article, recent progress in the development and application of calcium phosphate (CP)-based composites use as IBS is reviewed. CP materials have been used widely for bone replacement because of their similarity to the mineral component of bone. The main limitation of bulk CP materials is their brittle nature and poor mechanical properties. There is significant effort to reinforce or improve the mechanical properties and injectability of calcium phosphate cement (CPC) and this review resumes different alternatives presented in this specialized literature. © 2010 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.calciu
Keywords: Additives; Bone; Calcium phosphate cement; Injectability; Injectable bone substitutes; Mechanical properties